Product-Service Systems Benefits and Barriers: An Overview of Literature Review Papers - Moro, Suzana R.; Cauchick-Miguel, Paulo Augusto; Mendes, Glauco Henrique de Sousa (International Journal of Industrial Engineering and Management, 2020)
Product-Service Systems (PSS) appears as an emergent subject, gaining the attention of many researchers, and an increasing interest of organizations. As many literature reviews have been conducted in PSS-related field, this paper aims to overview publications from 2006 to 2018 by highlighting PSS benefits and barriers. Content analysis was used to codify data collected in the publications. The main characteristics of the literature reviews are provided as well as a set of 36 PSS benefits and 24 barriers organized in categories and sub-categories. Analyzing PSS-related review papers allows identifying future research opportunities which can foster the design and implementation of PSS business models. Article history: Received (October 11, 2019); Revised (February 20, 2020); Accepted (February 21, 2020); Published online (March 4, 2020)